(untitled) (Islas, 2018)
Este estudio posee como objeto la determinación de los atributos diferenciadores de Villa Clara, con el fin de generar conocimiento para la creación y gestión de marcas territorio en Cuba. Se desarrolló un análisis de las potencialidades históricas, culturales, sociales y turísticas del territorio a través de una metodología mixta, y un enfoque predominantemente cualitativo. Los hallazgos fundamentales se centran en la definición de los atributos villaclareños en función de la proyección de su identidad. The objective of this study is the determination of the differentiating attributes of Villa Clara, with the purpose of generating knowledge for the creation and administration of place brands in the country. An analysis of the historical, cultural, social and tourist potentialities of the territory was developed through a mixed methodology, and a mainly qualitative focus. The main results are focused in the definition of the history and the culture like attributes of Villa Clara in function of the projection of their identity.